Public information in rural areas : technology experiment (PIRATE) - Phase II - Clarke, J.E. (British Library LondonGB, 1989)
Focuses on how the project developed and reorganised methods of public access to information. Presents guidelines for setting up community information systems, and gives details of the costs that may be anticipated. Describes the integration of PIRATE into Devon Library Services, and looks at possible future developments and expansions of its community information management system.